Group dynamics : basics and pragmatics for practitioners - Haynes, Norris (University Press of America, 2012)
This book provides a clear and engaging description of group dynamic processes. Group Dynamics will serve as an important text for students and professors and as a valuable guide for those who facilitate groups in a variety of.